Production of Pectin-Cellulose Biofilms: A New Approach for Citrus Waste Recycling. (29th October 2017) - Bátori, Veronika; Jabbari, Mostafa; Åkesson, Dan; Lennartsson, Patrik R.; Taherzadeh, Mohammad J.; Zamani, Akram
Abstract : While citrus waste is abundantly generated, the disposal methods used today remain unsatisfactory: they can be deleterious for ruminants, can cause soil salinity, or are not economically feasible; yet citrus waste consists of various valuable polymers. This paper introduces a novel environmentally safe approach that utilizes citrus waste polymers as a biobased and biodegradable film, for example, for food packaging. Orange waste has been investigated for biofilm production, using the gelling ability of pectin and the strength of cellulosic fibres. A casting method was used to form a film from the previously washed, dried, and milled orange waste. Two film-drying methods, a laboratory oven and an incubator shaker, were compared. FE-SEM images confirmed a smoother film morphology when the incubator shaker was used for drying. The tensile strength of the films was 31.67 ± 4.21 and 34.76 ± 2.64 MPa, respectively, for the oven-dried and incubator-dried films, which is within the range of different commodity plastics. Additionally, biodegradability of the films was confirmed under anaerobic conditions. Films showed an opaque appearance with yellowish colour.